Effects of developmental stage, cold acclimation and diet on the cold tolerance of three species of Cryptolestes (Coleoptera: Laemophloeidae). (March 2021) - Ganesan, Lavanya; Fields, P.G.; Jayas, D.S.; Jian, F.
Abstract: Flat grain beetles (Coleoptera: Laemophloeidae) are common stored-product insect pests in Canada, infesting cereals in grain bins, equipment and end products in flour mills. We studied the cold tolerance of the three most common flat grain beetles: Cryptolestes ferrugineus, Cryptolestes turcicus and Cryptolestes pusillus, by measuring the survival at −10 °C and supercooling point (SCP) for different life stages (egg, young larva, old larva, pupa and adult) reared on flour mixed with brewer's yeast. Probit analysis was used to estimate the lethal time for 50 and 95% mortality. This was done with non-acclimated individuals (only held at 30 °C) or cold-acclimated individuals (held at 18, 10 and 5 °C, for 1 week/temperature). In general, adults were the most cold-hardy stage for each of the species. Acclimated insects were anywhere from no increase in cold tolerance to 14-fold more cold-tolerant than the corresponding non-acclimated stage and species. Cryptolestes ferrugineus was most cold-tolerant species (58 d at −10 °C to reach 95% mortality for acclimated adult), C. turcicus was the next most cold-tolerant, (39 d) and C. pusillus was the least cold-tolerant (11 d). The cold tolerance of adults reared on three diets was measured both for acclimated and non-acclimated insects. The adults reared on grain diet (whole wheat kernels, cracked wheat kernels and wheat germ (90:5:5 mass ratio) were the most cold-tolerant, adults reared on white-wheat flour and brewer's yeast diet (95:5 mass ratio) had the next highest cold tolerance followed by the adults reared on 100% white-wheat flour. Supercooling point (SCP) of insects ranged from −20.6 to −26.7 °C. In general, acclimated insects had slightly lower SCP than non-acclimated insects. Highlights: Survival at −10 °C and SCP of 3 Cryptolestes species measured for different stages. The effect of diet and cold acclimation was also tested. The adults were the most cold-tolerant stage for all species. Acclimation increased cold tolerance, diet affected cold tolerance. Cold tolerance from least to greatest was; C. pusillus, C. turcicus, C. ferrugineus.